INTERCULTURAL PRAGMATICS IN ENGLISH-UZBEK COMMUNICATION: CHALLENGES FOR EFL LEARNERS - Zokirova Marjona Xislatjon qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation : This paper explores the challenges faced by Uzbek EFL learners in understanding and applying intercultural pragmatics during English-Uzbek communication. It examines how cultural differences in speech acts, politeness strategies, and conversational norms affect communication effectiveness. The study highlights common pragmatic failures and their impact on learners’ language competence and intercultural awareness. Based on classroom observations and learner feedback, the paper suggests pedagogical approaches to enhance pragmatic competence, including the integration of cultural content and communicative practice in EFL curricula.